A scoping review of the additive manufacturing of mandibular implants - Winarso, Rochmad; Ismail, Rifky; Anggoro, Paulus Wisnu; Jamari, Jamari; Bayuseno, Athanasius Priharyoto (Frontiers in Mechanical Engineering, 2023)
Bone disease and fractures are among the health issues that are becoming more prevalent year after year. A mandibular disorder is caused by an accident or disease to the largest and strongest bone in the human face. Because the natural healing process of mandibular bones takes a long time, a bone grafting procedure is used to speed up the patient's recovery. Due to the limitations of bone grafting processes such as autographs, allographs, and xenografts, bone replacement is being developed using biomaterials via 3D printing. The purpose of the review was to evaluate research on the use of 3D printing in the replacement of mandible bones. The search algorithm found as many as 2941 articles at the start of the search and 123 articles after initial selection. After an initial screening that included the year, publication stage, source type, and language, as many as 70 articles were obtained, and after filtering titles and abstracts obtained 55 articles, 32 articles were included in this review. As a result, the field of additive manufacturing for the repair and reconstruction of mandibular defects necessitates the development of novel tools and methodologies. A customized biological scaffold can be created using an appropriate 3D printing process based on the characteristics of various mandibular defects, allowing it to be perfectly matched to the defect region and reducing stress, thereby improving the scaffold's healing function.